Visualizing Narrative Structures and Learning Style Information in Personalized e-Learning Systems - CONLAN, OWEN (IEEE, 2007)
This paper proposes a novel approach to the visualization of complex, but interrelated, sets of information to ease user cognition. Principally, it explores the potential of providing users of personalized e-Learning systems with a means of visualizing the complex space in which they learn, with the aim of supporting the development of meta- cognitive insight pertaining to their individual learning style. It also provides course authors with a novel means of understanding how learners used their courses over time, thereby enabling them to detect usage patterns and diagnose problems.
PUBLISHED
Keywords: cognition; computeraided instruction